Graphene oxide supported gold nanoclusters for the sensitive and selective detection of nitrite ions1. Issue 5 (7th March 2015) - Xu, Hongda; Zhu, Houjuan; Sun, Mingtai; Yu, Huan; Li, Huihui; Ma, Fang; Wang, Suhua
<x xml:space="preserve">Abstract</x> Nitrite selectively reacts to red fluorescent gold nanoclusters supported on blue fluorescent graphene oxide sheet and leads to a ratiometric fluorescence color change.